LANGUAGE INTERFERENCE ON ENGLISH: [n] ARTICULATION OF INDONESIAN STUDENTS - Susiati Susiati; Malikatul Laila; Qanitah Maskuroh (Universitas Muhammadiyah Surakarta, 2010)
Being familiar in “tahsin” rule in Arabic may have influenced ones in pronouncing regressive assimilation [n] in English. The study aims to identify the similarities and differences between English and Arabic with “tahsin” rules based onthe place of articulation and to describe how the students of Mu’allimat programpronounce regressive assimilation [n] in English. The data collected are the English speech produced by the students of Mu’allimat program in PONPES AlMukmin Ngruki Sukoharjo having “tahsin” background, especially English consonants and regressive assimilation [n] and Arabic “nun sakinah” law in “tahsin”rules. The data are analyzed by technique of comparing Arabic and English viewedfrom rules on phonetic base. The results show that (1) the similarities and differences between English consonant sounds and Arabic with “tahsin” rules lies in itsplace of articulation; and (2) the students of Mu’allimat program belonging tokhalaqoh tahsinul qur’an have not always pronounced English regressive assimilation [n]better than those who don’t belong to khalaqoh tahsinul qur’an.Key words: interference, regressive assimilation, tahsin.